Enabling Inclusive Sport Participation: Effects of Disability and Support Needs on Constraints to Sport Participation. (2nd January 2017) - Darcy, Simon; Lock, Daniel; Taylor, Tracy
ABSTRACT: Framed by a social approach to disability and leisure constraints theory, this paper presents the results of a national study examining the constraints to sport participation for people with disability. Responses were obtained from a multi-platform questionnaire survey capturing data on constraints to participation, dimensions of disability, and level of support needs. The Exploratory Factor Analysis identified five structural together with intrapersonal and interpersonal constraint factors. While intrapersonal and interpersonal considerations were found to constrain sport participation and nonparticipation, the five structural factors had the most significant constraining impact on sport participation. The findings showed that disability type and level of support needs explain significant variations in constraints to participation and nonparticipation. When the 2-Way MANOVA included type of disability and level of support needs as contingent independent variables, the level of support needs was the most significant indicator of the likelihood of having constraints to participation or nonparticipation.